LITERATURE REVIEW DIVERSITY IN ORGANIZATIONS: BIBLIOMETRIC ANALYSIS - Anis Sya’bania; Sopiah (Bajang Institute, 2022)
Diversity in organizations is very important today. With diversity, organizations can get various views, abilities, and various things to overcome organizational or company problems and increase the company's effectiveness. These differences can also lead to happiness and conflict in an organization. This literature review research uses bibliometric analysis. The articles used in the study were compiled from Google Scholar's database. This research aims to provide an in-depth study of diversity in organizations. There were 34 articles analyzed in this study. The research uses the Google Scholar database between 2017 and 2021 and uses PoP software to search for article data to be researched. After all the data has been collected, it will then be analyzed using VOSviewer software to analyze co-authorship and co-occurrence. A citation will be processed by using PoP software. The results of literature studies with a bibliometric analysis approach are expected to be a reference to provide an overview of diversity